Effect of Radiation on MHD Convective Flow and Heat Transfer of a Viscoelastic Fluid Over a Stretching Surface. (2015) - Eswaramoorthi, S.; Bhuvaneswari, M.; Sivasankaran, S.; Rajan, S.
Abstract: The Problem of three-dimensional MHD convective boundary layer flow and heat transfer of a viscoelastic fluid in the presence of radiation was examined. A similarity transformation is used to reduce the governing non-linear partial differential equations into ordinary differential equations and then they are solved using homotopy analysis method (HAM). Graphical results for the velocity and temperature profiles are displayed and discussed. Numerical results for the local Nusselt number is tabulated for various values of the parameters.